Experimenter Effects on Pain Reporting in Women Vary across the Menstrual Cycle. (29th March 2015) - Vigil, Jacob M.; DiDomenico, Jared; Strenth, Chance; Coulombe, Patrick; Kruger, Eric; Mueller, Andrea A.; Guevara Beltran, Diego; Adams, Ian
Abstract : Background . Separate lines of research have shown that menstrual cycling and contextual factors such as the gender of research personnel influence experimental pain reporting. Objectives . This study examines how brief, procedural interactions with female and male experimenters can affect experimentally reported pain (cold pressor task, CPT) across the menstrual cycle. Methods . Based on the menstrual calendars 94 naturally cycling women and 38 women using hormonal contraceptives (M age = 19.83, SD = 3.09 ) were assigned to low and high fertility groups. This assignment was based on estimates of their probability of conception given their current cycle day. Experimenters (12 males, 7 females) engaged in minimal procedural interactions with participants before the CPT was performed in solitude. Results . Naturally cycling women in the high fertility group showed significantly higher pain tolerance (81 sec, d = .79 ) following interactions with a male but not a female experimenter. Differences were not found for women in the low fertility or contraceptive groups. Discussion . The findings illustrate that menstrual functioning moderates the effect that experimenter gender has on pain reporting in women. Conclusion . These findings have implications for standardizing pain measurement protocols and understanding how basic biopsychosocial mechanisms (e.g., person-perception systems) can modulate pain experiences.